Contributions of inner and outer coordination sphere bonding in determining the strength of substituted phenolic pyrazoles as copper extractants. Issue 7 (14th January 2016) - Healy, Mary R.; Roebuck, James W.; Doidge, Euan D.; Emeleus, Lucy C.; Bailey, Philip J.; Campbell, John; Fischmann, Adam J.; Love, Jason B.; Morrison, Carole A.; Sassi, Thomas; White, David J.; Tasker, Peter A.
Abstract : Simple phenolic pyrazoles have strengths and selectivities comparable to oxime extractants which account for a quarter of the world's copper production. Abstract : Alkyl-substituted phenolic pyrazoles such as 4-methyl-2-[5-( n -octyl)-1 H -pyrazol-3-yl]phenol (L2H) are shown to function as Cu-extractants, having similar strength and selectivity over Fe(iii ) to 5-nonylsalicylaldoxime which is a component of the commercially used ACORGA® solvent extraction reagents. Substitution in the phenol ring of the new extractants has a major effect on their strength, e.g. 2-nitro-4-methyl-6-[5-(2, 4, 4-trimethylpentyl)-1 H -pyrazol-3-yl]phenol (L4H) which has a nitro group ortho to the phenolic hydroxyl group unit and has an extraction distribution coefficient for Cu nearly three orders of magnitude higher than its unsubstituted analogue 4-methyl-6-[5-(2, 4, 4-trimethylpentyl)-1 H -pyrazol-3-yl]phenol (L8H). X-ray structure determinations and density functional theory (DFT) calculations confirm that inter-ligand hydrogen bonding between the pyrazole NH group and the phenolate oxygen atom stabilise the Cu-complexes, giving pseudomacrocyclic structures. Electron-accepting groups ortho to the phenol oxygen atoms buttress the inter-ligand H-bonding, enhancing extractant strength but the effectiveness of this is very dependent on steric factors. The correlation between the calculated energies of formation of copper complexes in the gas phase and the observed strength of comparably substituted reagents in solvent extraction experiments is remarkable. Analysis of the energies of formation suggests that big differences in strength of extractants arise principally from a combination of the effects of the substituents on the ease of deprotonation of the proligands and, for the ortho -substituted ligands, their propensity to buttress inter-ligand hydrogen bonding.